Experiences Influencing upon the Significance of Obstetric Care in Mexican Nurses - Consuelo Martínez Villa; Yesica Rangel Flores (Investigación y Educación en Enfermería, 2018)
Objective. This work sought to learn which and how are the professional experiences that influence upon significance processes of obstetric care in nurses working in toco-surgery rooms.